Applying for research funding. Part 2 – Writing a grant application. (July 2016) - Nelson, Adam W; Lamb, Alastair D; Gnanapragasam, Vincent J
Objective: The process of writing a grant application can be challenging. In this article we summarise key aspects of the process including when to begin, whom to submit to and how to construct a research hypothesis. It is intended that this article will be a useful resource for individuals seeking to embark on research as part of a higher degree.